Migrant returns Manila, development, and transnational connectivity - Pido, Eric J. (Durham Duke University Press, 2017)
Eric J. Pido examines the complicated relationship between the Philippine economy, Manila’s urban development, and Filipino migrants visiting or returning to their homeland, showing migration to be a multidirectional, layered, and continuous process with varied and often fraught outcomes.
Introduction: An ethnography of return -- Departures -- The Balikbayan economy: Filipino Americans and the contemporary transformation of Manila -- The foreign local: Balikbayans, overseas Filipino workers, and the return economy -- Transnational real estate: selling the American dream in the Philippines -- Returns -- The Balikbayan hotel: touristic performance in Manila and the anxiety of return -- The Balikbayan house: the precarity of return migrant homes -- Domestic affects: the Philippine retirement authority, retiree visas, and the national -- Discourse of homecoming -- Conclusion: Retirement landscapes and the geography of exception.
Includes bibliographical references and index.
Keywords: Return migration -- Philippines; Filipino Americans -- Migrations; Philippines. -- Emigration and immigration